2.45 GHZ RECTENNA DESIGN FOR RF ENERGY HARVESTING - Meor Said, M.A.; Zakaria, Z.; Husain, M.N.; Misran, M.H.; Yunus, M.M.; Ismail, M.M; Abu Khadrah, A. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
A high conversion efficiency rectenna at 2.45 GHz is proposed in this paper. Two layers low cost FR-4 substrate has been used to fabricate the rectenna. The proposed designs contain patch antenna and open stub rectifying circuits. The dimension for the proposed rectenna design is 100 x 100 x 5 mm3. The technique of air gap approach has been used in order to increase gain of the antenna. The ground plane is added with the triangular slot has eliminate second and third harmonics which results enhancement of the conversion efficiency. The measured conversion efficiency reaches 79.29% when the input power at 17 dBm. This rectenna takes advantages of low profile, easy integration, high gain and high power conversion efficiency from previous proposals.